New insights into the activation mechanism of ammonium ions on the malachite sulfidization flotation - Liu, Mengfei; Chen, Daixiong; Hu, Bo; He, Peng; Chen, Yaozong; Zeng, Huimin; Zhang, Chenyang; Zhu, Jianyu (Minerals engineering, 2024)
[Display omitted] •Found that NH4+ eliminated the inhibitory effect of Cu2+ on sulfidization.•Found that NH4+ worked with Cu2+ to further promote sulfidization.•Reveal the mechanism of action between NH4+ and Cu2+.•Reveal the effects of Cu2+ and Cu(NH3)42+ on surface sulfidization. Ammonium sulfate [(NH4)2SO4] is an effective activator of malachite sulfidization flotation. In this work, we explored the effects of ammonium ion (NH4+) and copper ion (Cu2+) on malachite sulfidization flotation and investigated the underlying mechanism. Flotation experiments demonstrated that NH4+ can not only eliminate the negative effects of Cu2+, but also work together with Cu2+ to further promote malachite sulfidization flotation in a certain concentration range. Zeta potential, SEM-EDS, and X-ray photoelectron spectroscopy analysis results indicated that the single Cu2+ weakened the oxidation of S (II) species on the malachite surface and reduced the formation of sulfides. In the presence of NH4+, Cu2+ did not inhibit the formation of sulfides on malachite surface but worked with NH4+ to promote it. Aqueous speciation calculation and adsorption test revealed that NH4+ and Cu2+ interacted to form Cu (II)–NH3 complexes, which reacts with S (II) species to form a copper sulfide substance that is more easily adsorbed on the malachite surface than the copper sulfide colloid formed by the reaction between Cu2+ and S (II) species. This leads to the improvement of surface sulfidization.